Identifying the Characteristics of the Student: An Evaluation for English Teachers Pedagogical Competence - Rahmad Risan (Universitas Negeri Padang, 2022)
This research aims to identify the pedagogical competences of the English Teachers based on identifying the characteristics of the student. This is one of the sub-competence that must be mastered as one indicator of pedagogical competence mastery. Where one of the competence is identifying students’ characteristics. it is explained as identifying the learner characteristics related with the competence of instructors to know the condition of the students.This research was conducted by using Descriptive Evaluation method. Whereas evaluative research is the systematic collection and analysis of data about the quality, effectiveness, merit, or value of programs, products, or practices. The result of the research showed All four teachers could understand or identify their students’ cognitive ability. They understand their students, not only the good students, but also the poor students. Besides identifying the students’ cognitive ability, it is also very important for the teacher to know about the learners’ personality in order that he/she can apply appropriate way in teaching the students with the different personality.